Applying New Media Techniques for Conveying News and Information by Journalists of Broadcasting News Channels: (a survey study) (Raparin Journal of Humanities (RJH), 2024)
Despite the fact that the new media through which people around the world are aware of the up-to-date developments as it is the most widespread form of communication, there are still confusions and unclarities among the journalists of news channels in delivering news and data. This research aims to know whether journalists and members of media have developed the new technics and taken advantage of them, or they had not improved. The distinction and selecting the most suitable applications that journalists increasingly use as new media technics require a scientific way of research in order to clear the confusion properly.This research is a scientific attempt to identify the level of awareness and usage of the new media technics by journalists of the Kurdish news channels through taking a sample of the channels’ correspondents that would indicate what suitable applications and how they are used as a new media technic. The research is qualitative and is conducted through surveys.  Questionnaires are responded to by 84 correspondents of the news channels, from which samples are intentionally taken. The respondents’ opinion is measured this way. A number of objectives have been achieved in this research. The most important one that the researcher has realized is that the majority of the journalists that work in the news channels are males. Additionally, the majority of the research sample indicates WhatsApp is the most used app. Recommendations are provided at the end of the research.